2008
DOI: 10.1111/j.1553-2712.2008.00235.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Computerized Provider Order Entry and Nursing Documentation on Workflow

Abstract: Objectives: The objective was to measure the effects of the implementation of computerized provider order entry (CPOE) and electronic nursing documentation on provider workflow in the emergency department (ED). Methods:The authors performed a before-and-after time-motion study of the activities of physicians and nurses. The percentages of time spent in task categories were calculated by provider session and averaged across provider sessions.Results: There was a shift in physician time from working with paper a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 11 publications
1
38
0
Order By: Relevance
“…Another study has shown that nurses concern about the implementation of EHR documentation and hence the time spent on the process of recording decreases the available time for procedures of direct patient care. These findings led to the conclusion that there were no helpful changes in patient-care procedures, workflow, and the time spent on documentation, and consequently no changes in quality of documentation (45). Moreover, several studies have shown that the speed, accessibility, location, and consistency of the computer and electronically established programs may also adversely affect the documentation process (46)(47)(48)(49).…”
Section: Discussionmentioning
confidence: 95%
“…Another study has shown that nurses concern about the implementation of EHR documentation and hence the time spent on the process of recording decreases the available time for procedures of direct patient care. These findings led to the conclusion that there were no helpful changes in patient-care procedures, workflow, and the time spent on documentation, and consequently no changes in quality of documentation (45). Moreover, several studies have shown that the speed, accessibility, location, and consistency of the computer and electronically established programs may also adversely affect the documentation process (46)(47)(48)(49).…”
Section: Discussionmentioning
confidence: 95%
“…19 Prior time-motion studies have quantified the impact of technology interventions on clinician workflow, 11,20,21 but to the best of our knowledge, the methodology…”
Section: Discussionmentioning
confidence: 99%
“…For example, the addition of health information technology (health IT) can have an effect on workflow, including how staff communicates and the way that teams operate; health IT is discussed in greater detail later. 15,16 Overcrowding Researchers have documented the negative effects of overcrowding on patient safety and patient satisfaction. 17 Overcrowding is associated with increased in-hospital mortality, increased rates of medical errors, and increased rates of patients both leaving the hospital without being seen and signing out against medical advice.…”
Section: -10mentioning
confidence: 99%